Collaborative Reading Strategy (CRS) in Improving EFL Students' Reading Comprehension - Jeihn Novita Ch. Budiman; Nindy Nource Ganap (Dinasti Publisher, 2025)
This research aims to examine the effectiveness of CRS strategies in improving reading comprehension skills of the students’ of Politeknik Pelayaran Sulawesi Utara. Using quantitative research through pre-experimental design with one group pre-test and post-test, the data analysis statistically carried out using descriptive analysis and Paired Sample T-test. To find that there is a significant effect of using Collaborative Reading Strategy (CRS), the data will be calculated by using SPSS 25.0 application. The results show that CRS strategies have been proven to be effective in improving students' reading comprehension skills. The CRS strategy used is able to help students develop interest in reading and overcome boredom in the learning process. The implementation of Collaborative Reading Strategy (CRS) strategies has proven to be highly effective in improving the reading comprehension skills of the 2nd semester Nautical students at Politeknik Pelayaran Sulawesi Utara. The study revealed a significant increase in students' comprehension abilities, as evidenced by the substantial rise in mean scores from the pre-test to the post-test. The study confirms that CRS is a valuable tool for improving reading comprehension skills among Nautical students. The significant improvement in scores demonstrates that CRS strategies are well-suited to the needs of students in specialized fields, where understanding complex texts is essential.